2019
DOI: 10.1101/668111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Life Supraphysiological Levels of Oxygen Exposure Permanently Impairs Hippocampal Mitochondrial Function

Abstract: Preterm infants requiring prolonged oxygen therapy often develop cognitive dysfunction later life. Previously, we reported that 14-week-old young adult mice exposed to hyperoxia as newborns had spatial memory deficits and hippocampal shrinkage. We hypothesized that the underlying mechanism was the induction of hippocampal mitochondrial dysfunction by neonatal hyperoxia. C57BL/6j mouse pups were exposed to 85% oxygen or air from P2 -P14.Hippocampal proteomic analysis was performed in young adult mice (14 weeks)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Downregulated expression of these proteins could lead to mitochondrial dysfunction, especially NDUS1, NU2M, or NDUV2, which are core subunits for function and structure of complex I in the mitochondria [ 51 , 52 ]. A similar finding on reduced expression of complex I mitochondrial proteins following 85% oxygen was previously reported [ 53 ] and hyperoxia-induced mitochondrial damage is also proposed to cause simplification of lung structure, or bronchopulmonary dysplasia (BPD) in infant lungs [ 54 ].
Fig.
…”
Section: Resultssupporting
confidence: 73%
“…Downregulated expression of these proteins could lead to mitochondrial dysfunction, especially NDUS1, NU2M, or NDUV2, which are core subunits for function and structure of complex I in the mitochondria [ 51 , 52 ]. A similar finding on reduced expression of complex I mitochondrial proteins following 85% oxygen was previously reported [ 53 ] and hyperoxia-induced mitochondrial damage is also proposed to cause simplification of lung structure, or bronchopulmonary dysplasia (BPD) in infant lungs [ 54 ].
Fig.
…”
Section: Resultssupporting
confidence: 73%
“…Several past studies have shown the beneficial effects of oxygen administration to patients with critical disorders (Bourke et al, 2018; Golledge & Singh, 2019; Jaber et al, 2016; Levy et al, 2016; Martin & Grocott, 2013; Moradkhan & Sinoway, 2010; Renda et al, 2018; Rockswold et al, 2013; Weaver et al, 2002) as well as to healthy individuals, such as athletes (Ishii et al, 2005; Kujawski et al, 2020). Conversely, the issue of oxygen toxicity is also well known, as molecular oxygen induces cell damage directly or indirectly by interacting with other free radicals (Ciarlone et al, 2019; Frank et al, 1978; Kuksal et al, 2017; Matute‐Bello et al, 2008; Ramani et al, 2019). Although the precise mechanism is yet to be completely understood, oxygen toxicity can largely vary depending on the types of cells/organs, the systemic/regional pathophysiological conditions, and the oxygen administration parameters (such as time, concentration, and pressure; Fandler‐Höfler et al, 2020; Frank et al, 1978; Matute‐Bello et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive oxygen exposure may induce severe damage to normal tissue (stem) cells; however, there remains an absence of consensus regarding the optimal oxygen concentration and administration duration under particular pathophysiological conditions. The harmful effects of oxygen intake at increased partial pressures are most often reflected in the central nervous system and lungs (Chu et al, 2018; Ciarlone et al, 2019; Davis et al, 1983; Ramani et al, 2019; Taccone et al, 2018). Therefore, the risk‐benefit balance based on individual pathophysiological conditions should be evaluated carefully, following which an optimal oxygen administration schedule should be designed to provide the optimum benefits (Brugniaux et al, 2018; Chu et al, 2018; Fandler‐Höfler et al, 2020; Lumb & Walton, 2012; Rocco et al, 2014; Taccone et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation